World Wide Web Audio: Ensuring Adequate Hardware And Software Configurations - Ang, Minni; Othman, Abu Talib; Tee, Elok Robert (Malaysian Journal of Computer Science, 1996)
As Client machines need to be properly configured with the correct hardware and software to playback the many different audio file formats available, a discussion of how to configure client machines is given.